A high-porosity carbon fiber base paper and its preparation method and application
By partially replacing carbon fiber as plant fiber in carbon fiber raw paper, and using low-temperature drying and enzymatic decomposition technology, the porosity of carbon fiber raw paper is significantly improved, and the problems of low porosity and mechanical performance in the existing technology are solved, achieving both high porosity and excellent mechanical performance.
Patent Information
- Application Number
- CN202510045301.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-12-24
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-04
AI Technical Summary
The low porosity of existing carbon fiber raw papers limits their performance in applications where high porosity is required, while methods that improve porosity often lead to decreased mechanical strength and poorer chemical stability.
By partially replacing the plant fibers with carbon fibers and molding them under the bonding of adhesives at low temperature drying film-forming temperature, the plant fibers were then enzymatically dissolved by cellulase, which significantly improved the porosity of the carbon fiber base paper.
While maintaining excellent mechanical properties and chemical stability, the porosity of carbon fiber raw paper is significantly improved and is suitable for a variety of industrial application scenarios.
Abstract
Description
Technical Field
[0001] The invention relates to high-porosity carbon fiber base paper and a preparation method and application thereof. Background Art
[0002] Existing carbon fiber base paper usually adopts a full carbon fiber structure with a low porosity of about 90%, which limits its performance in application scenarios that require high porosity. Lower porosity will lead to a reduction in the specific surface area of the material, which in turn affects its efficiency in applications such as electrochemical reactions and adsorption. In order to improve the porosity of carbon fiber base paper, current research and industrial practice usually adopt methods such as adjusting the density and arrangement of fibers and heat treatment.
[0003] Although the above methods have their own advantages, they all have some obvious limitations, such as the decrease in mechanical strength of carbon fiber base paper, the deterioration of chemical stability (fiber oxidation after high temperature heat treatment), and the complex process and high cost. Therefore, it is necessary to develop a new process to prepare carbon fiber base paper, so that the porosity of carbon fiber base paper can be improved while maintaining its excellent mechanical properties and chemical stability. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide an improved method for preparing carbon fiber base paper in view of the shortcomings and deficiencies of the prior art. The carbon fiber base paper prepared by the preparation method has significantly improved porosity while maintaining excellent mechanical properties and chemical stability.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing carbon fiber base paper, the preparation method comprising the following steps: mixing carbon fiber, plant fiber and adhesive to obtain slurry; performing papermaking and drying on the slurry to obtain a carbon fiber base paper precursor; performing enzymolysis on the carbon fiber base paper precursor in the presence of cellulase to obtain the carbon fiber base paper; the drying film-forming temperature of the adhesive is 50-100°C.
[0007] In the present invention, drying and film formation refers to the volatilization of the solvent in the adhesive system and the film formation of the components in the adhesive, and this process does not necessarily require the addition of a curing agent. Many polymer adhesives can be dried and cured to form a film without the presence of a curing agent.
[0008] In the prior art, the porosity of carbon fiber base paper is usually improved by adjusting the density and arrangement of fibers, heat treatment and other methods, however, adjusting the density and arrangement of fibers may cause the mechanical strength of carbon fiber base paper to decrease, and heat treatment is usually carried out at a higher temperature (e.g., higher than 100 ° C), and the fiber is usually oxidized after high temperature treatment, resulting in its chemical stability deteriorating. The inventor of the present application has found through research that by partially replacing carbon fiber with plant fiber, and forming under the bonding of adhesives with lower drying film-forming temperature, and drying, the adhesive film is formed and cured during drying, so that carbon fiber and plant fiber form a preliminary combined network structure, ensuring that the two can be firmly combined during the molding process, and obtaining a carbon fiber base paper precursor, and then using cellulase to enzymolyze the plant fiber part in the precursor, so that the pores corresponding to the plant fiber part are exposed, and then the porosity of carbon fiber base paper is further increased. Due to the low drying film-forming temperature of the adhesive, and the mild enzymolysis conditions, the temperature is low, so the entire process temperature of the present application is relatively low, avoiding the oxidation of the fibers in the carbon fiber base paper, and ensuring its chemical stability and mechanical strength.
[0009] In some embodiments, the adhesive is selected from polyvinyl butyral (PVB, drying film-forming temperature is about 90° C.) and / or polyvinyl alcohol (PVA, drying film-forming temperature is about 80° C.).
[0010] In some embodiments, the plant fiber is hardwood fiber; preferably bleached hardwood fiber; more preferably a combination of one or more selected from eucalyptus fiber, poplar fiber, and birch fiber.
[0011] In some embodiments, the carbon fiber has a diameter of 7-10 μm and a length of 5-10 mm.
[0012] In some embodiments, the plant fiber has a diameter of 10-20 μm and a length of 1-3 mm.
[0013] In some embodiments, the mass ratio of the carbon fiber to the plant fiber is 6-9:1-4.
[0014] In some embodiments, the mass ratio of the carbon fiber to the adhesive is 25-1000:1; preferably 300-600:1.
[0015] In some embodiments, the adhesive is in the form of a solution.
[0016] Preferably, the mass percentage of the adhesive in the adhesive solution is 2%-10%.
[0017] In some embodiments, the adhesive is a polyvinyl butyral solution with a mass percentage of 5%-10%. The solvent can be an alcohol solvent such as ethanol or methanol.
[0018] In some embodiments, the adhesive is a polyvinyl alcohol solution with a mass percentage of 2%-8%. The solvent can be an alcohol solvent such as ethanol or methanol.
[0019] In some embodiments, the papermaking process is wet papermaking process.
[0020] In some embodiments, the drying temperature is 80-100° C. This drying temperature will not cause fiber oxidation, thus ensuring its chemical stability.
[0021] In some embodiments, the drying time is 1-2 hours.
[0022] In some embodiments, the enzymatic hydrolysis is performed at a pH of 5-7.
[0023] In some embodiments, during the enzymatic hydrolysis, the mass concentration of the substrate is 3%-5%. The substrate for enzymatic hydrolysis is the plant fiber in the carbon fiber base paper precursor, and the mass concentration of the substrate represents the mass concentration of the plant fiber in the enzymatic hydrolyzate, wherein the mass of the plant fiber is calculated based on the feed mixed with the carbon fiber in the previous step.
[0024] In some embodiments, during the enzymatic hydrolysis, the enzyme activity is 100-500 IU / ml.
[0025] In some embodiments, the cellulase is in the form of a solution.
[0026] In some embodiments, the enzymatic hydrolysis temperature is 40-50° C. This enzymatic hydrolysis temperature is mild and will not affect the chemical stability of the fiber.
[0027] In some embodiments, the enzymatic hydrolysis time is 4-8 hours.
[0028] In some embodiments, the enzymatic hydrolysis is performed under stirring.
[0029] Furthermore, the stirring speed may be 60-100 rpm. Slow stirring may be added during the enzymatic hydrolysis process to improve the removal efficiency of the plant fibers.
[0030] In some embodiments, the preparation method further comprises the steps of washing and drying after the enzymatic hydrolysis.
[0031] Furthermore, washing is performed by water to clean the carbon fiber base paper to remove residual enzymatic hydrolysis products.
[0032] Furthermore, the drying temperature is 60-80° C. and the drying time is 1-3 hours. Washing and drying can further ensure the stability of the pore structure and mechanical strength of the carbon fiber base paper.
[0033] The present invention further provides a carbon fiber base paper prepared by the method for preparing the carbon fiber base paper. The carbon fiber base paper has a significantly improved porosity while maintaining excellent mechanical properties and chemical stability.
[0034] In some embodiments, the porosity of the carbon fiber base paper is 90.5%-97%, preferably 94%-96%.
[0035] In some embodiments, the carbon fiber base paper has a tensile strength of 3-4 MPa.
[0036] In some embodiments, the carbon fiber base paper has a thickness of 200-300 μm.
[0037] The present invention further provides use of the carbon fiber base paper as an electrode material.
[0038] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0039] The present invention proposes a new method of partially replacing carbon fiber with plant fiber and then removing the plant fiber by enzymatic hydrolysis, which significantly improves the porosity of carbon fiber base paper. The method mixes plant fiber with carbon fiber during the manufacturing process, stabilizes the material structure by using a low-temperature drying film-forming adhesive, and then uses a mild enzymatic hydrolysis method to remove the plant fiber and retain the carbon fiber network, thereby improving the porosity of the material while ensuring mechanical strength and thermal stability. This new process avoids high-temperature treatment or complex composite processes in traditional methods, has the advantages of low cost and high efficiency, and is suitable for a variety of industrial application scenarios.
[0040] The present invention combines the addition of plant fibers and enzymatic treatment and selects a suitable adhesive with a low drying film-forming temperature, thereby significantly improving the porosity of the carbon fiber base paper while ensuring the excellent mechanical properties and chemical stability.
[0041] The porosity of the carbon fiber base paper of the present invention can be as high as 94% or more, while the tensile strength is maintained at more than 3MPa, and because it has not been subjected to high-temperature treatment, it has excellent chemical stability. DETAILED DESCRIPTION
[0042] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention, but the present invention is not limited to the scope of the examples.
[0043] In the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art.
[0044] Example 1
[0045] This embodiment provides a carbon fiber base paper, and the preparation method thereof is as follows:
[0046] 1. Raw materials preparation:
[0047] Carbon fiber: 7μm in diameter and 6mm in length;
[0048] Bleached poplar fiber: 12 μm in diameter and 2-3 mm in length;
[0049] Polyvinyl butyral (PVB) solution: PVB is dissolved in ethanol at a mass concentration of 10%;
[0050] Cellulase solution: enzyme activity is 200 IU / ml, pH value is 6, used at a temperature of 45°C.
[0051] 2. Slurry preparation steps:
[0052] Mix the carbon fiber and bleached poplar fiber in a mass ratio of 7:3 and put them into a blender;
[0053] A 10% mass concentration PVB solution was added to the mixture, wherein the mass ratio of PVB to carbon fiber in the PVB solution was 500:1, and the mixture was stirred for 30 minutes to uniformly disperse the fibers to obtain a slurry.
[0054] 3. Papermaking steps:
[0055] The prepared slurry was papered using a wet papermaking device to form a product with a thickness of 200 μm.
[0056] 4. Low temperature drying and curing steps:
[0057] The papermaking product is placed in a drying furnace and dried at a temperature of 90° C. for 2 hours to ensure that the PVB is completely cured and a stable paper structure is formed to obtain a carbon fiber base paper precursor.
[0058] 5. Enzymatic hydrolysis steps:
[0059] The dried carbon fiber base paper precursor was placed in a cellulase solution with a substrate mass concentration of 3% and an enzyme activity of 200 IU / ml, and soaked at 45°C for 6 hours while stirring at 80 rpm;
[0060] After the enzymatic hydrolysis was completed, the carbon fiber base paper was taken out and washed three times with deionized water to remove the enzymatic hydrolysis products and residues.
[0061] 6. Post-processing and drying steps:
[0062] The cleaned carbon fiber base paper was placed in a drying furnace again and dried at 60°C for 1 hour to ensure that the pore structure of the paper was stable, thereby obtaining the final carbon fiber base paper product.
[0063] Example 2
[0064] This embodiment provides a carbon fiber base paper, and the preparation method thereof is as follows:
[0065] 1. Raw materials preparation:
[0066] Carbon fiber: 5μm in diameter and 8mm in length;
[0067] Bleached poplar fiber: 15 μm in diameter and 1-2 mm in length;
[0068] Polyvinyl alcohol (PVA) solution: with a mass concentration of 8%, PVA was dissolved in ethanol;
[0069] Cellulase solution: enzyme activity is 300 IU / ml, pH value is 5.5, used at a temperature of 40°C.
[0070] 2. Slurry preparation steps:
[0071] Mix carbon fiber and bleached poplar fiber in a mass ratio of 8:2 and put them into a blender;
[0072] A PVA solution with a mass concentration of 8% was added to the mixture, wherein the mass ratio of PVA to carbon fiber in the PVA solution was 400:1, and the mixture was stirred for 40 minutes to uniformly disperse the fibers to obtain a slurry.
[0073] 3. Papermaking steps:
[0074] The prepared slurry was papered using a wet papermaking device to form a product with a thickness of 280 μm.
[0075] 4. Low temperature drying and curing steps:
[0076] The papermaking product was placed in a drying furnace and dried at 80°C for 1 hour to ensure that the PVA was completely cured into a film and a stable bonding structure was formed to obtain a carbon fiber base paper precursor.
[0077] 5. Enzymatic hydrolysis steps:
[0078] The dried carbon fiber base paper precursor was placed in a cellulase solution with a substrate mass concentration of 5% and an enzyme activity of 500 IU / ml, and soaked at 40°C for 8 hours with a stirring speed of 70 rpm;
[0079] After the enzymatic hydrolysis was completed, the carbon fiber base paper was taken out and washed twice with deionized water to remove the enzymatic hydrolysis products.
[0080] 6. Post-processing and drying steps:
[0081] The cleaned carbon fiber base paper was placed in a drying furnace again and dried at 85°C for 3 hours to ensure that the pore structure and mechanical strength were stable, thereby obtaining the final carbon fiber base paper product.
[0082] Example 3
[0083] This embodiment provides a carbon fiber base paper, and the preparation method thereof is basically the same as that of Embodiment 1, except that the bleached poplar fiber is replaced by the bleached eucalyptus fiber.
[0084] Example 4
[0085] This embodiment provides a carbon fiber base paper, and its preparation method is basically the same as that of Embodiment 1, except that the bleached poplar fiber is replaced by the bleached birch fiber.
[0086] Comparative Example 1
[0087] This comparative example provides a carbon fiber base paper, and the preparation method thereof is as follows:
[0088] 1. Raw materials preparation:
[0089] Carbon fiber: 7μm in diameter and 6mm in length;
[0090] Polyvinyl butyral (PVB) solution: PVB is dissolved in ethanol at a mass concentration of 10%.
[0091] 2. Slurry preparation steps:
[0092] Place carbon fiber in blender;
[0093] A 10% mass concentration PVB solution was added to the carbon fiber, the mass ratio of PVB in the PVB solution to the carbon fiber was 500:1, and the mixture was stirred for 30 minutes to uniformly disperse the fibers to obtain a slurry.
[0094] 3. Papermaking steps:
[0095] The prepared slurry was papered using a wet papermaking device to form a product with a thickness of 200 μm.
[0096] 4. Low temperature drying and curing steps:
[0097] The papermaking product is placed in a drying furnace and dried at a temperature of 90° C. for 2 hours to ensure that the PVB is completely cured and a stable paper structure is formed to obtain a carbon fiber base paper.
[0098] Comparative Example 2
[0099] This comparative example provides a carbon fiber base paper, and the preparation method thereof is as follows:
[0100] 1. Raw materials preparation:
[0101] Carbon fiber: 5μm in diameter and 8mm in length;
[0102] Polyvinyl alcohol (PVA) solution: PVA is dissolved in ethanol at a mass concentration of 8%.
[0103] 2. Slurry preparation steps:
[0104] Place carbon fiber in blender;
[0105] A PVA solution with a mass concentration of 8% was added to the carbon fiber, wherein the mass ratio of PVA to the carbon fiber in the PVA solution was 400:1, and the mixture was stirred for 40 minutes to uniformly disperse the fibers to obtain a slurry.
[0106] 3. Papermaking steps:
[0107] The prepared slurry was papered using a wet papermaking device to form a product with a thickness of 200 μm.
[0108] 4. Low temperature drying and curing steps:
[0109] The papermaking product was placed in a drying furnace and dried at 80°C for 1 hour to ensure that the PVA was completely cured into a film and a stable paper structure was formed to obtain a carbon fiber base paper.
[0110] Comparative Example 3
[0111] This comparative example provides a carbon fiber base paper, and its preparation method is basically the same as that of Example 1, except that: the ethanol solution of PVB is replaced by the ethanol solution of phenolic resin, maintaining the mass concentration at 10%; and the drying temperature of step 4 is adjusted to 150°C.
[0112] According to GB / T 20042.7-2014 standard, the properties of the carbon fiber base paper prepared in each embodiment and comparative example were tested, and the results are shown in Table 1 below.
[0113] Table 1 Properties of carbon fiber base paper in various embodiments and comparative examples
[0114] Porosity (%) Tensile strength(MPa) Example 1 95.7 3.21 Example 2 94.6 3.71 Example 3 95.2 3.50 Example 4 93.6 3.43 Comparative Example 1 90.1 3.44 Comparative Example 2 88.3 4.02 Comparative Example 3 87.4 4.50
[0115] From the comparison between Example 1 and Comparative Example 1, it can be seen that the porosity of the carbon fiber base paper after enzymatic hydrolysis is increased from the original 90.1% to 95.7%, and the tensile strength is only reduced by 0.23MPa; from the comparison between Example 2 and Comparative Example 2, it can be seen that the porosity of the carbon fiber base paper after enzymatic hydrolysis is increased from the original 88.3% to 94.6%, and the tensile strength is only reduced by 0.31MPa. That is, the process of the present invention can significantly improve the porosity under the premise of ensuring high tensile strength. Although the strength of Comparative Example 3 is higher, the porosity is not enough to 90%, which is difficult to be used in the field of electrode materials.
[0116] In addition, the PVB or PVA used in the embodiment can be dried and cured to form a film at a relatively low temperature (below 100°C), avoiding the drying or hot pressing temperature higher than 100°C in the traditional carbon fiber base paper manufacturing process, and avoiding the fiber transition keratinization and difficulty in enzymatic hydrolysis. The phenolic resin used in Comparative Example 3 has a curing film-forming temperature of about 130-170°C, which will cause plant fiber keratinization at such a high temperature, making it difficult for the carbon fiber base paper precursor to be enzymatically hydrolyzed, and ultimately resulting in a low porosity of the carbon fiber base paper.
[0117] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
[0118] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
Claims
1. A method for preparing carbon fiber base paper, characterized in that: The preparation method comprises the following steps: mixing carbon fiber, plant fiber and adhesive to obtain slurry; performing papermaking and drying on the slurry to obtain a carbon fiber base paper precursor; performing enzymolysis on the carbon fiber base paper precursor in the presence of cellulase to obtain the carbon fiber base paper; the drying film-forming temperature of the adhesive is 50-100°C.
2. The method for preparing carbon fiber base paper according to claim 1, characterized in that: The adhesive is selected from polyvinyl butyral and / or polyvinyl alcohol.
3. The method for preparing carbon fiber base paper according to claim 1, characterized in that: The plant fiber is hardwood fiber; preferably bleached hardwood fiber; more preferably a combination of one or more selected from eucalyptus fiber, poplar fiber, and birch fiber.
4. The method for preparing carbon fiber base paper according to claim 1, characterized in that: The carbon fiber has a diameter of 7-10 μm and a length of 5-10 mm; and / or the plant fiber has a diameter of 10-20 μm and a length of 1-3 mm.
5. The method for preparing carbon fiber base paper according to claim 1, characterized in that: The mass ratio of the carbon fiber to the plant fiber is 6-9:1-4; and / or the mass ratio of the carbon fiber to the adhesive is 25-1000:
1.
6. The method for preparing carbon fiber base paper according to claim 1, characterized in that: The adhesive exists in the form of a solution; preferably, the mass percentage of the adhesive in the adhesive solution is 2%-10%.
7. The method for preparing carbon fiber base paper according to claim 6, characterized in that: The adhesive is selected from a polyvinyl butyral solution with a mass percentage of 5%-10% or a polyvinyl alcohol solution with a mass percentage of 2%-8%.
8. The method for preparing carbon fiber base paper according to claim 1, characterized in that: The papermaking process is wet papermaking process; and / or the drying temperature is 80-100° C.; and / or the drying time is 1-2 hours.
9. The method for preparing carbon fiber base paper according to claim 1, characterized in that: The enzymolysis is carried out at a pH of 5-7; and / or, during the enzymolysis, the mass concentration of the substrate is 3%-5%; and / or, during the enzymolysis, the enzyme activity is 100-500 IU / ml.
10. The method for preparing carbon fiber base paper according to claim 1, characterized in that: The cellulase is in the form of a solution; and / or the temperature of the enzymolysis is 40-50° C.; and / or the time of the enzymolysis is 4-8 hours; and / or the enzymolysis is performed under stirring.
11. The method for preparing carbon fiber base paper according to claim 1, characterized in that: The preparation method further comprises the steps of washing and drying after the enzymatic hydrolysis.
12. A carbon fiber base paper prepared by the method for preparing carbon fiber base paper according to any one of claims 1 to 11.
13. The carbon fiber base paper according to claim 12, characterized in that: The porosity of the carbon fiber base paper is 90.5%-97%; and / or, the tensile strength of the carbon fiber base paper is 3-4MPa; and / or, the thickness of the carbon fiber base paper is 200-300μm.
14. Use of the carbon fiber base paper according to claim 12 as an electrode material.